Effects of Different Salt Applications on Ion and Physiological Analysis in Lettuce - Turgay Kabay (Turkish Journal of Agriculture: Food Science and Technology, 2022)
The increase in salinization in agricultural lands adversely affects crop production. In particular, yield and quality losses occur in many vegetables such as lettuce, which are grown and consumed in every season. Realizing these losses in crop production, more careful fertilization and agricultural practices should be done. Yedikule lettuce seeds were used in the study to draw attention to these negative aspects. The study, which was carried out for two years, was designed with 0, 50, 100 and 150 mmol doses of salt according to a randomized parcel design with three replications and four pots in each replicate. Each 2-liter pot was filled with a 2:1 ratio of peat: perlite mixture and the study was carried out with 2 lettuces in each pot. As a result of the study, when the plant weight data of the first year and the second year are examined, it is seen that the weight loss of lettuce plants and damage to the plants increase when the salt doses increase. It was observed that the highest plant weight loss occurred at 150 mmol salt dose. Membrane damage index in lettuce leaves was observed to increase as the salt dose increased. It was observed that the leaf water rate decreased with increasing salt doses. Membrane damage index and leaf water content of lettuce plants were more negatively affected at 150 mmol of salt in both years. Potassium, calcium and magnesium contents in lettuce leaves were statistically decreased due to increasing salt doses in both years, while sodium content increased with increasing salt doses and the highest sodium content was observed at 150 mmol dose in both years. As seen in these results, increasing salt doses reduce the nutrient content and plant weight in lettuce plants and cause physiological damage to the plant, resulting in yield and quality loss.